Reforming the International Financial Architecture: The East Asian View - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 2000)
Despite the measures that have already been put in place to strengthen the international financial architecture in the wake of the Asian financial crisis, still much remain to be done. This paper tried to distinguish developing economies views, in general, and East Asian views, in particular, on reforming the international financial architecture from the G7 and G7-led institutions views and found substantial differences. From East Asias and developing economies perspective, the present discussions on reforming the international financial architecture that take place mainly within G7 and G7-led institutions are unlikely to lead to solutions for the prevention of future crises. East Asias and developing economies concern regarding the governance structure for reforming the international financial architecture and the Bretton Woods Institutions, establishment of regional financial arrangement, and some of the substantive aspects of the proposed reform package deserve to be given utmost consideration in discussions on strengthening the international financial system.
Keywords: 330; Asian financial crisis; financial market